Overactive bladder - Anna Zwierzyńska (Kazimierz Wielki University, 2021)
Urinary incontinence is a problem among both older and young women. The most common symptoms of this condition include urinary incontinence and an unpleasant odour. In order to conceal the ailments related to this problem, women change their lifestyle by limiting the amount of fluid consumed and not moving too far from home or places where toilets are located. The main source of information on this disease in women aged over 45 is books, magazines and websites. Medical personnel are only ranked behind them. In order to make a correct diagnosis of this disease and to start treatment, urodynamic examination, urinalysis, cystoscopy and imaging examinations should be performed. Urodynamic examination can be divided into two groups: invasive and non-invasive. The micturition diary is considered to be the basic urodynamic test. It allows for performing differential diagnosis of functional micturition disorders. It is characterized by high repeatability and correlation with clinical symptoms. Treatment options are dependent on the type of urinary incontinence. They may include conservative treatment, surgery and pharmacotherapy. Combining conservative methods with pharmacological or surgical methods brings the most beneficial results. Invasive methods are the last-line therapy.